Organizational structure of public schools in relation to leadership skills and management styles of secondary administrators in the Division of Calamba City - Senadoza, Andrea C. (Manila : National University, 2009)
This study was delimited to the Organizational Structure of Public Schools in relation to leadership skills and management styles of Secondary Administrators in the Division of Calamba City with an end view of establishing the extent of their effectiveness on school management during school year 2009-2010.
Chapter 1: The Problem and its Setting -- Chapter 2. Review of Related Literature and Studies -- Chapter 3. Research Design and Methodology -- Chapter 4. presentation, Analysis and Interpretation of Data -- Chapter 5. Summary, Conclusion and Recommendations -- Bibliography -- Appendices -- Curriculum Vitae .
Research Design: Descriptive Method.
Includes bibliographical references.